PENGARUH BAURAN PEMASARAN 4P (PRODUK, PRICE, PLACE, PROMOTION) DAN KUALITAS PELAYANAN BERBASIS SYARIAH TERHADAP KEPUTUSAN KONSUMEN UNTUK MEMBELI DI TOKO YUNIKA JABON SIDOARJO - Abdillah Mundir; Anita Agustining Rahayu (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Marketing means everything that producers can offer to be noticed, requested, sought, bought, used or consumed by the market as a fulfillment of the needs or desires of the relevant market, while sharia marketing is a business strategy that must cover all activities within a company, covering the entire process, creating , offering, exchange of value, services, from a producer, or a company or individual, in accordance with Islamic teachings. The approach used by researchers in this study is a quantitative approach with multiple linear regression, t test, and f test using data collection techniques through questionnaires. Meanwhile, the instrument used in this research is the Likert scale. Based on the results of the research and the results of the regression analysis that has been carried out, the following conclusions can be drawn: 1) The marketing mix has a significant effect on consumer buying decisions at Yunika Stores. This is indicated by the value of thecalculated is greater than the Ttable (7.272 > 2.00665). 2) The quality of sharia-based service has a significant effect on consumer decisions to buy at Yunika Stores. This is indicated by the Tcount is greater than the Ttable (6.020 > 2.00665). 3) Marketing mix and service quality have a joint effect on consumer buying decisions at Yunika Stores with Fcount greater than Ftable (27.828 > 3.17).